Human Values in the Megengan Tradition in Post-Covid-19 in Indonesia - Muh, Moh Muhtador; Erina Dwi Parawati (Human Sustainability Procedia, 2022)
The COVID-19 pandemic has caused chaos in human thoughts, attitudes and behavior that have an impact on life, both materially and morally. This article examines the role of community traditions in maintaining human values ​​in the aftermath of the COVID-19 pandemic. The purpose of this paper is to present the role of tradition for society after the COVID-19 pandemic which focuses on three main points, namely the meaning of tradition, implementation and the values ​​contained by tradition. This research was taken by means of observation, documentation and interviews with village and religious leaders, village heads and residents who carry out the megengan tradition. The findings of this article are that the megengan tradition has a special meaning for the community, namely as a medium to foster solidarity, because in practice it involves many people interacting with each other and the megengan tradition contains human values ​​that are described in solidarity, awareness and humanity.